Analisis Manajemen Proyek Aplikasi Pembelajaran Biologi Berbasis Android - Mustari, Dewi; Nadeak, Theresia Evy Yulianty; Ningsih, Retna (JURSIMA, 2022)
The trend of using technology is currently growing rapidly, especially in the field of education. As a result of the current pandemic, all learning is done online. Apart from all that, to improve the quality of each school competing in creating learning media as a tool in improving the quality of human resources, especially students. SMP X will build an android-based biology learning application as a new learning medium to improve students' understanding of biology learning materials, this application was created not to replace classroom learning but as an additional learning method by utilizing technology. Of course, before designing this android-based biology learning application, service providers must prepare various needs for the system to be built, the duration of the work and calculate the costs that must be spent. The method used in this research is a literature study of various cases in journals or articles that discuss the problem of software project management analysis according to the schedule and costs set so as to produce a descriptive analysis. The results of this study are an overview of system requirements, work schedules and costs that will be issued